Child Tracker: Presence and Location Finding System to Protect Child from Missing and Unexpected Cases - G. Senthilnathan (Institute of Advanced Engineering and Science, 2017)
Many times children on their own are getting away from parent's view at home or on crowded areas like malls and beach. Not in all cases, but rather from time to time it is unpretentious the kids and hopeless things happening moreover. So it is fundamental for each parent to have a dominating reaction for shield the child from missing. However, the couple of GPS based after things are open in the market, they cost high and also needs a month to month charge for GSM advantage. Energize GPS is significant for outside after and not for nearby spots like strip shopping centers or houses. Also, the things accessible in the market are not viewing the improvement of a young wearing it. Our answer utilizes two contraptions for parent and tyke, clear RF correspondence between gadgets, virtual fencing using RF and tyke improvement viewing. The parent and child can wear this device rather than watch since it displays time data to them.